Methodological Basis of the Induction Problem - Skersytė, Jūratė (Problemos, 1974)
The article aims at revealing the gnoseological content of the arguments which sprang up historically and still continue to arise around the so-called problem of induction. On the basis of the concrete historical material the methodological prerequisites of the emergence of the induction problem are disclosed, the attention being paid to the relationship of the methodological lines of Humean and neopositivistic criticism of induction. The very history of the inductive logic development from the traditional (Bacon-Mill) to the modern (probability) is considered to be the proof of the methodological groundlessness of the contemplative gnoseology which saw an autonomous basis of cognition in the individual experience. The author comes to the conclusion that the methodological groundlessness of the contemplative gnoseology makes the statement of the induction problem baseless too.